Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/his.14180
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse alveolar damage (DAD) resulting from coronavirus disease 2019 Infection is Morphologically Indistinguishable from Other Causes of DAD

Abstract: Diffuse alveolar damage (DAD) resulting from coronavirus disease 2019 Infection is Morphologically Indistinguishable from Other Causes of DAD Aims: Diffuse alveolar damage (DAD) is a ubiquitous finding in inpatient coronavirus disease 2019 (COVID-19)-related deaths, but recent reports have also described additional atypical findings, including vascular changes. An aim of this study was to assess lung autopsy findings in COVID-19 inpatients, and in untreated severe acute respiratory syndrome coronavirus 2 (SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
180
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(220 citation statements)
references
References 20 publications
19
180
1
10
Order By: Relevance
“…Pulmonary histopathologic changes related to ARDS are usually similar regardless of its etiology [4][5][6][7]. This observation can be extended to cases caused by SARS-CoV-2 infection [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pulmonary histopathologic changes related to ARDS are usually similar regardless of its etiology [4][5][6][7]. This observation can be extended to cases caused by SARS-CoV-2 infection [7].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary histopathologic changes related to ARDS are usually similar regardless of its etiology [4][5][6][7]. This observation can be extended to cases caused by SARS-CoV-2 infection [7]. In 2007 Mandal et al reported abnormalities in platelet homeostasis including an increase in the number of pulmonary MKs in patients with DAD [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most important histological lesions observed during autopsy of patients who died from SARS-CoV-2 infection.LungReferences Diffuse alveolar damage (histological hallmark of SARS-CoV-2 infection)[15][16][17][18][19][20][21][22][23][24] Focal vasculitis and capillaritis associated to microthrombosis as direct viral effect Thrombosis of large and medium-size pulmonary, related to SARS-COV-2-associated coagulopathy (likely secondary to an endothelial damage related to direct viral infection of the endothelial cells) or deriving from the deep veins of the lower extremities. Superimposed bronchopneumonia as result of bacterial superinfectionHeartMyocardial damage and myocarditis associated with increase in troponin levels, related to (a) direct myocardial infection by SARS-CoV-2 (b) hypoxemia due to respiratory failure and (c) inflammatory response correlated to the severe systemic inflammation status.…”
mentioning
confidence: 99%